Classification of kinesiophobia in patients after cardiac surgery under extracorporeal circulation in China: latent profile and influencing factors analysis from a cross-sectional study - Qi Li; Rong Wang; Yanmei Gu; Tong Ren; Jing Jing Piao; Wenhui Xing; Yujing Liang (BMJ Open)
Objective To investigate the potential classification of kinesiophobia in patients after cardiac surgery under extracorporeal circulation from a psychosocial perspective, and analyse the characteristic differences among different latent levels of patients.Study design This is a cross-sectional study of Chinese adults after cardiac surgery under extracorporeal circulation, aged 18 years and older, recruited from a tertiary hospital in North China.Methods This study uses latent profile analysis to identify potential classifications of kinesiophobia in questionnaires from 348 patients undergoing cardiac surgery under extracorporeal circulation. Multiple logistic regression analysis was used to evaluate the influencing factors at different latent classifications.Results The average performance of each indicator in Model 3 is best suited for analysis, Entropy=0.873 and bootstrap likelihood ratio test (p)＜0.0001. The result of regression equation shows postoperative time (p<0.001), age, self-efficacy, pain and social support level (p<0.05) were the factors influencing the potential profile classification of patients after cardiac surgery under extracorporeal circulation.Conclusion The study identified three distinct classifications of patients: the low kinesiophobia group, the moderate kinesiophobia—high-risk perceived symptoms group and the high kinesiophobia—high exercise avoidance group (HK-HEAG). Addressing kinesiophobia, especially in older male patients during the early postoperative period, is crucial. Enhancing self-efficacy seems effective in reducing kinesiophobia, while increasing social support may not be as beneficial for the HK-HEAG. These findings provide a basis for implementing preventive interventions in cardiac rehabilitation.Trial registration number The research is registered with the Chinese Clinical Trial Registry (ChiCTR2200057895).